PETANI KELAPA SAWIT DI NAGARI INDERAPURA KECAMATAN PANCUNG SOAL KABUPATEN PESISIR SELATAN (Studi Sejarah Sosial Ekonomi Tahun 2000-2011) - Yendra, Lince; Naldi, Hendra; Nazmi, Ranti (Pendidikan Sejarah, 2013)
ABSTRACT This writing works through around farmer oil palm at silvan inderapura districts to bite off regency problem south beach: studi is economic sociological history, of year 2000 - 2011. There is formula even problem at observational it is as follows: early its input its oil palm at silvan inderapura, and it retreats its oil palm term at inderapuras village. As history of studis economic social, to the effect this paper for influence plant wide see oil palm goes to inderapuras farmer societyThis paper writing utilize history research method that consisting of four steps which is heuristic (sought after and data collecting), source criticism, interpretation, and historiografi (writing)Year 2000 is made as limitation of inscriptive startups because since that year society at silvan inderapura starts energetic plant out oil palm at its farm. To the effect this writing to know how economic social situation inderapuras society, after its input oil palm plant. Before marks sense society oil palm plant at silvan inderapura relies coffee plant as source of its economy. Transition of this coffee plant is reverential because cumbersome more coffee plant its processing, and despitefully coffee plant also been attacked disease pest, and inadequate to meet the need life. Year 2001 is made as bounds of this inscriptive final because gets to increase farmer life level oil palm, it visually deep article of luxury possession, clothing, and food and fixed up house and society at silvan inderapura can no longer rely oil palm as source of its economy because its sell point is down. Oil palm agricultural have given meaning impact for farmer economy social which is at the height society income at silvan inderapura. There is impact even that felt by farmer amongst those, first, it accomplishes farmer economy requirement. Both of, farmer can set apart one part of good oil palm sell result to be saved or even to be bought high-value goodses as gold as and furnitures family. Third, their oil palm farmer can build their house gets better of previously, e.g. Just build permanent house. Fourth, anxious beginning farmer to school their childs to superordinate ladder as smp or on a level, sma or on a level or even to college. To five increases it is ardour societies will their health, since with have their money more gets to get doctor to hospital or to hospital if they are taking ill.